FLOW FIELD PLATE DESIGN ANALYSIS WITH CROSS-SECTION WAVE RECTANGULAR SERPENTINE USING 3D FLOW SIMULATION ON PROTON EXCHANGE MEMBRANE FUEL CELL - Teguh Imam Prasetya; Deni Shidqi Khaerudini (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
The availability of petroleum which continues to decrease and the level of public consumption which is always increasing are serious problems today. Renewable energy needs to be researched on an ongoing basis to anticipate the availability problems above. Proton Exchange Membrane Fuel Cell (PEMFC) is an environmentally friendly source of electrical energy because it only requires hydrogen and oxygen as raw materials and water as a result of the reaction. This study will discuss the PEMFC flow field plate because this component dominates the weight and cost of manufacture. Research on flow field plate PEMFC with wave rectangular cross-section is necessary to develop the PEMFC concept with better performance results. This study aims to determine the effect of the wavy cross-section shape on the distribution of channel average speed, channel outlet speed, inlet pressure, channel average pressure, and channel outlet pressure. This study uses a computational fluid dynamic (CFD) method using SolidWorks flow simulation software. This study provides an overview of the serpentine type of flow field plate with a wave rectangular and rectangular cross-section. The wave rectangular cross-section has a higher average velocity, outlet velocity, inlet pressure, and pressure than the rectangular cross-section. This is what will make PEMFC performance higher. The wave rectangular cross-section has nearly the same number of outlet pressures as the rectangular cross-section. Possible development of this research is the creation of simulation software to calculate other parameters that affect PEMFC performance.